Implementation Of Drip Irrigation On The Growth Of Pagoda Mustard (Brassica narinosa L.): Implementasi Irigasi Tetes pada Budidaya Sawi Pagoda (Brassica narinosa L.) - Qaanitatul Hakim Ipaulle; Jihan Azzah Muthi'ah; Siti Azizah Ardiningtyas; Indriyanti Widyaratna (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2025)
Drip irrigation has been applied as an alternative irrigation technology for cultivating pagoda mustard in arid areas. This study aimed to evaluate the effects of different drip irrigation frequencies on the growth of pagoda mustard (Brassica narinosa L.). The experiment was conducted from September to December 2024 at the Agrotechnology Experimental Field, Faculty of Science and Technology, University of Darussalam Gontor. Four irrigation treatments were applied: conventional surface watering (control), drip irrigation once per day, drip irrigation twice per day, and drip irrigation three times per day. Each treatment was replicated three times. Observed parameters included microclimatic conditions and plant growth variables. Data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test at the 5% significance level when significant differences were detected, using RStudio software. The results showed that drip irrigation was able to meet the water requirements for pagoda mustard growth. No significant differences were observed in root and shoot growth among treatments; however, drip irrigation applied three times per day enhanced shoot canopy growth compared to lower irrigation frequencies.